X-ray photoelectron spectroscopy of Sn₂P₂S₆ crystals - Grigas, J.; Talik, E.; Lazauskas, V.; Vysochanskii, Yu.M.; Yevych, R.; Adamiec, M.; Nelkinas, V. (Condensed Matter Physics, 2008)
The paper presents the X-ray photoelectron spectra (XPS) of the valence band (VB) and of the core levels (CL) of uniaxial ferroelectric Sn₂P₂S₆ single crystals from different crystallographic planes in both paraelectric and ferroelectric phases. The XPS were measured with monochromatized Al Kα radiation in the energy range 0 1400 eV. The VB consists of five bands with the maxima between 3.3 eV and 14.5 eV below the Fermi level. Experimental energies of the VB and core levels are compared with the results of theoretical ab initio calculations of the molecular model of the Sn₂P₂S₆ crystal. The electronic structure of the VB is revealed. Ferroelectric phase transition changes the atom's charge and strength of the bonds, electronic structure of VB, width of CL lines and chemical shifts for the Sn, P and S states which are crystallographic plane-dependent.